sub.1-Adrenoceptor Autoantibodies from DCM Patients Enhance the Proliferation of T Lymphocytes through the [beta].sub.1-AR/cAMP/PKA and p38 MAPK Pathways - Du, Yunhui; Yan, Li; Wang, Jin; Zhan, Wenzhang; Song, Kai; Han, Xue; Li, Xiao; Cao, Jimin; Liu, Huirong (PloS one, 2012)
Autoantibodies against the second extracellular loop of the [beta].sub.1 -adrenergic receptor ([beta].sub.1 -AA) not only contribute to increased susceptibility to heart failure, but also play a causative role in myocardial remodeling through their sympathomimetic-like effects that are induced upon binding to the [beta].sub.1 -adrenergic receptor. However, their role in the function of T lymphocytes has never been previously investigated. Our present study was designed to determine whether [beta].sub.1 -AA isolated from the sera of dilated cardiomyopathy (DCM) patients caused the proliferation of T cells and the secretion of cytokines. Blood samples were collected from 95 DCM patients as well as 95 healthy subjects, and [beta].sub.1 -AA was detected using ELISA. The CD3.sup.+ T lymphocytes were selected separately through flow cytometry and the effect of [beta].sub.1 -AA on T lymphocyte proliferation was examined by CCK-8 kits and CFSE assay. Western blotting was used to analyze the expressions of phospho-VASP and phospho-p38 MAPK. [beta].sub.1 -AA enhanced the proliferation of T lymphocytes. This effect could be blocked by the selective [beta].sub.1 -adrenergic receptor antagonist metoprolol, PKA inhibitor H89, and p38 MAPK inhibitor SB203580. Furthermore, the expression of the phosphorylated forms of phospho-VASP and phospho-p38 MAPK were markedly increased in the presence of [beta].sub.1 -AA. [beta].sub.1 -AA also inhibited the secretion of interferon-[gamma] (IFN-[gamma]) while promoting an increase in interleukin-4 (IL-4) levels. These results demonstrate that [beta].sub.1 -AA isolated from DCM patients binds to [beta].sub.1 -AR on the surface of T cells, causing changes in T-cell proliferation and secretion through the [beta].sub.1 -AR/cAMP/PKA and p38 MAPK pathways.